2013
DOI: 10.1002/fuce.201200161
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Characteristics of Electrolytes Assessed with Resonant Ultrasound Spectroscopy

Abstract: Elastic properties and residual stresses are critical for the assessment of the reliability of ceramics components. The thin electrolyte layer of anode supported SOFCs is under a state of high compressive residual stress. In the present study, the elastic properties of this layer as well as the residual stress distribution induced in the anode‐supported planar SOFC cell were examined by using the resonant ultrasound spectroscopy (RUS). A modal analysis by finite element simulation demonstrated that the RUS has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…It was found that a 20 MPa residual stress (which is close to the tensile failure stress) with a 5 mm thick substrate results in an output beam radius of ~ 680 m and the corresponding curvature measurement would be beyond the measurement capability of available instrumentation [46]. A recent paper by Araki et al [47] have used a combination of finite element (FE) and RUS technique to determine the elastic properties of the electrolyte. However, the use of this technique is limited by the number of layers in the multilayer specimen and the corresponding analysis gets complicated for more than 3 layers.…”
Section: Uniaxial Tensile Response: Multilayer Ceramic Specimensmentioning
confidence: 99%
“…It was found that a 20 MPa residual stress (which is close to the tensile failure stress) with a 5 mm thick substrate results in an output beam radius of ~ 680 m and the corresponding curvature measurement would be beyond the measurement capability of available instrumentation [46]. A recent paper by Araki et al [47] have used a combination of finite element (FE) and RUS technique to determine the elastic properties of the electrolyte. However, the use of this technique is limited by the number of layers in the multilayer specimen and the corresponding analysis gets complicated for more than 3 layers.…”
Section: Uniaxial Tensile Response: Multilayer Ceramic Specimensmentioning
confidence: 99%
“…Recently, some studies have been carried out on the relationship between residual stress and the physical features of the specimen [3][4]. For mechanical systems vibration signal, the IMF components reflect the nature vibration mode function which contain physical features [5].…”
Section: Introductionmentioning
confidence: 99%